Application of total reflection X-Ray fluorescence spectrometry to quantify cobalt concentration in the presence of high iron concentration in biogas plants. Issue 2 (7th February 2020) - Arthur, Richard; Scherer, Paul
Abstract: The concentration of iron is usually several times higher than of cobalt in many environmental samples. Total Reflection X-ray Fluorescence Spectrometry can be used for monitoring in the ppb range, due to its high sensitivity and rapid multi elemental analysis capability. Unfortunately, cobalt/iron-spectra exhibit interference, because the energy line of iron (Kβ) overlaps the energy line of cobalt (Kα). As a result, the concentration of cobalt measured usually appears to be lower than the actual concentration or even below detection limit. In this study, application of dispersive liquid-liquid micro-extraction procedure was used to selectively extract iron in order to enable accurate cobalt determination. The volume of hydrochloric acid, volume of ethyl ether, number of stages of extraction and the duration of extraction were considered with the purpose of obtaining elaborated optimum extraction conditions. The sensitivity and linearity of the method were determined using liquid and solid samples through spike experiments. This new procedure was successfully applied to slurries of biogas plants having total solids content in the range of 7–12%. It was possible to estimate dissolved cobalt concentration of 50 µg L −1 in the presence of 4000-fold iron concentration. Also, recoveries of between 75–84% was obtained after spiking 10–20 µg L −1 of cobalt, whiles recoveries of above 94% were obtained after spiking cobalt concentrations >20 µg L −1 after application of the procedure.